New generation formulations of agrochemicals : current trends and future priorities - Volova, T. G. e uthor; Shishatskaya, Ekaterina I.; Zhila, Natalia O.; Prudnikova, Svetlana V.; Boyandin, Anatoly N. (Oakville, ON ; Palm Bay, Florida : Apple Academic Press, 2019)
"This important volume provides new research on the design and application of ecologically safe formulations for protecting cultivated crops against pathogen-causing diseases and weeds--that also provide nitrogen fertilizers at the same time. The authors make a significant contribution to the development and agricultural use of environmentally safe and biodegradable new-generation pesticides with targeted and controlled release of active ingredients. They discuss the problems associated with the use and accumulation of xenobiotics in the biosphere and present highlights of modern trends in the design of new-generation formulations. The authors present their original research results on the properties of herbicides, fungicides, and nitrogen fertilizers deposited in a degradable polymer base and the effectiveness of the use of these formulations in laboratory ecosystems with higher plants infected with fusariosis and weeds. The research provided here provides a new direction for the use of degradable polymers, essential for the creation of ecologically safe agricultural technologies and reducing uncontrolled accumulation and spread of xenobiotics in the biosphere. The book will be valuable for biotechnologists, chemists, material scientists, plant physiologists, and teachers and students of biological departments of universities."--
Agrochemicals: usage and associated environmental issues -- Polyhydroxyalkanoates: natural degradable biopolymers -- Biodegradation behavior of polyhydroxyalkanoates -- Experimental formulations of herbicides and evaluation of their efficacy -- Characterization of experimental formulations of the fungicide tebuconazole and their efficacy -- Slow-release formulations of nitrogen fertilizers and evaluation of their efficacy.
OCLC-licensed vendor bibliographic record.
Keywords: Agricultural chemicals; SCIENCE / General; SCIENCE / Life Sciences / Biochemistry